2018
DOI: 10.1097/md.0000000000010197
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of circulating cell-free DNA in breast cancer

Abstract: Background:Circulating cell-free DNA (cfDNA) isolated from plasma or serum by noninvasive procedures can serve as a “liquid biopsy” and has potential as a biomarker for the tumor burden and survival prediction of breast cancer (BC). However, its prognostic value in patients with BC is currently under debate. The aim of this meta-analysis was to investigate the relationship between cfDNA and survival outcome.Methods:We systematically searched PubMed, Embase, and Science Citation Index electronic databases for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 27 publications
0
29
0
2
Order By: Relevance
“…While large meta-analyses ( Table 2 ) have confirmed the prognostic relevance of CTCs, the existing data on circulating DNA is much less extensive ( Table 3 ). A meta-analysis published in 2018 by Tan et al included a total of 1127 patients from 10 trials, the majority with non-metastatic disease 22 . Unlike in the pooled analyses on CTC significance, the populations here were markedly smaller (336 patients maximum).…”
Section: Clinical Applications Of Liquid Biopsy In Early Breast Cancementioning
confidence: 99%
See 1 more Smart Citation
“…While large meta-analyses ( Table 2 ) have confirmed the prognostic relevance of CTCs, the existing data on circulating DNA is much less extensive ( Table 3 ). A meta-analysis published in 2018 by Tan et al included a total of 1127 patients from 10 trials, the majority with non-metastatic disease 22 . Unlike in the pooled analyses on CTC significance, the populations here were markedly smaller (336 patients maximum).…”
Section: Clinical Applications Of Liquid Biopsy In Early Breast Cancementioning
confidence: 99%
“…3 ). In einer 2018 veröffentlichten Metaanalyse von Tan et al wurden insgesamt 1127 Patientinnen aus 10 Studien berücksichtigt, der Großteil im nicht metastasierten Setting 22 . Anders als in den gepoolten Analysen zur Relevanz von CTCs waren hier die Kollektive deutlich kleiner (max.…”
Section: Verbesserung Der Prognoseeinschätzungunclassified
“…Bettegowda et al [17] reported that ctDNA was detectable in > 75% of patients with advanced breast carcinoma, compared to 50% of those with localized tumors. Recently, a large metaanalysis including 10 studies examined the prognostic relevance of cell-free DNA (cfDNA) in 1127 patients with BC [18] . Six studies examined only patients with early BC (stages I-III, n = 840), two studies included metastatic patients (stage IV, n = 183), and two studies included both groups (stages I-IV, n = 104).…”
Section: Prognosticationmentioning
confidence: 99%
“…In addition, the MRI high cost, the long holding up list in developing countries and the inaccurate result of imaging techniques (Kuhl, 2019). So, finding diagnostic biomarkers may be a useful alternative choice (Tan et al 2018).…”
Section: Introductionmentioning
confidence: 99%